Dynamic contrast enhanced MR imaging for rectal cancer response assessment after neo‐adjuvant chemoradiation. Issue 6 (14th August 2014) - Intven, Martijn; Reerink, Onne; Philippens, Marielle E.P.
<x xml:space="preserve">Abstract</x> Background Patient selection for organ sparing treatment after good response to neo‐adjuvant chemoradiation (CRT) for locally advanced rectal cancer is challenging as no optimal restaging modality is available after CRT. In this study, we assessed the value of dynamic contrast enhanced magnetic resonance imaging (DCE‐MRI) for rectal cancer pathological response prediction. Methods In 51 patients with locally advanced rectal cancer, the tumor volume and volume transfer constant (Ktrans) were obtained at 3 Tesla before CRT and surgery. The predictive potential for pathological complete response (pCR) and good response (GR) was assessed. GR was defined as pCR and near‐pCR based on the tumor regression grade. Results The GR group consisted of 10 patients (19.6%) with six pCR (11.8%). Both the post‐CRT tumor volume and post‐CRT Ktrans values and the relative change in volume (ΔVolume) and Ktrans (ΔKtrans) were predictive for pathological response. ΔKtrans showed the best predictive potential with a positive predictive value (PPV) of 100% for GR using a cutoff value of 32% reduction in Ktrans. For pCR the best PPV was 80% with a multiparameter model containing ΔVolume and ΔKtrans. Conclusion DCE‐MRI has predictive potential for pathological response after CRT in rectal cancer with the relative ΔKtrans being the most predictive parameter.J. Magn. Reson. Imaging 2015;41:1646–1653. © 2014 Wiley Periodicals, Inc.